27 dresses [videorecording (DVD)] - Fletcher, Anne, 1966-; Heigl, Katherine; Greer, Judy, 1975-; Marsden, James, 1973- (20th Century Fox Home Entertainment, 2008)
Jane has the kind of selflessness that everyone looks for in a friend. Lately the perennial bridesmaid has begun to feel as if something is missing in her life. Kevin is a local newspaper reporter who spots Jane racing between two receptions - one in Manhattan and the other in Brooklyn. He quickly surmises that her quirky tale may be just the story to get him into the big leagues. Jane butts heads with Kevin just as her younger sister, Tess, shows up in town. Now, Jane is prompted to reevaluate her priorities when her boss - with whom she is secretly in love - falls for her younger sister. As the bride-to-be makes plans to marry, she mistakenly assumes Jane will be happy to take part in the wedding. Jane finally comes to terms with her true feelings and her life begins to change in ways she never expected.